EFFECT OF IRON-MOLYBDENUM NANOCLUSTER POLYOXOMETALATES ON THE FUNCTIONAL ACTIVITY OF MACROPHAGES AND THE STATE OF BONE MARROW ERYTHROBLASTIC ISLANDS - A. A. Titova; M. O. Tonkushina; A. A. Ostroushko; M. V. Ulitko; S. A. Brilliant; I. G. Danilova (Медицинская иммунология, 2019)
AbstractThe aim of this study was to determine the mechanisms of action of Mo72Fe30 on erythropoiesis and hematological parameters *in vitro* and *in vivo*. The obtained results showed that neither the nanocluster polyoxometalate Mo72Fe30 nor its destruction products (low-molecular-weight iron and molybdenum-containing ions) affected the activity of non-specific esterase in the cytoplasm of central macrophages of bone marrow erythroblastic islands, thus indicating no disruption of endotoxin and xenobiotic detoxification processes carried out by these macrophages. However, administration of the studied substances resulted in a decrease in macrophage phagocytic capacity without altering cellular involvement in phagocytosis.Analysis of erythroblastic island cultures revealed the following patterns: administration of Mo72Fe30 and its destruction products (PD) accelerated erythroid cell maturation within the erythroblastic island corona. At 24 hours after their administration, a decrease in the number of class 3 and involutive erythroblastic islands was observed due to accelerated maturation and dissociation of erythroblastic islands. This process was confirmed by an increase in the number of erythroid cells in the myelogram at 24 hours after these substances administration. The simultaneous increase in the number of reconstructing erythroblastic islands in the groups treated with the polyoxometalate and its PD suggests the development of an additional wave of erythropoiesis within the island corona. On day 2 after administration of Mo72Fe30, there was an increase in the number of proliferating erythroblastic islands of the class 2 and 3, while the number of class 1 islands remained unchanged. This is attributed to the involvement of new macrophages into erythropoiesis and active erythroid cells proliferation. On day 3, a shift towards a more mature proliferating erythroblastic islands of the class 2 was observed. These data indicate the acceleration of erythrocyte maturation within erythroblastic islands after 3 days of the Mo72Fe30 administration. A similar trend was observed with the PD administration, although the erythropoiesis-accelerating effect was less pronounced.Analysis of rat bone marrow myelograms revealed an increase in bone marrow cellularity after seven days of administration of the studied substances (Mo72Fe30 and PD). This increase was attributed, in part, to an increase in the number of erythroid cells and reticulocytes.These data are consistent with peripheral blood parameters in rats. A statistically significant increase in erythrocyte count, hemoglobin levels, and hematocrit values was observed following administration of the studied substances (Mo72Fe30 and PD).The experimental results suggest a potential stimulatory effect on erythroid lineage development.